Molecular Modeling of the Three-Dimensional Structure of Human Sphingomyelin Synthase - 张亚 林赋 邓晓东 王任小 叶德泳 (Chinese journal of chemistry, 2011)
Sphingomyelin synthase （SMS） produces sphingomyelin and diacylglycerol from ceramide and phosphatidyl- choline. It plays an important role in cell survival and apoptosis, inflammation, and lipid homeostasis, and therefore has been noticed in recent years as a novel potential drug target. In this study, we combined homology modeling, molecular docking, molecular dynamics simulation, and normal mode analysis to derive a three-dimensional struc- ture of human sphingomyelin synthase （hSMS 1） in complex with sphingomyelin. Our model provides a reasonable explanation on the catalytic mechanism of hSMS 1. It can also explain the high selectivity of hSMS 1 towards phos- phocholine and sphingomyelin as well as some other known experimental results about hSMS1. Moreover, we also derived a complex model of D609, the only known small-molecule inhibitor of hSMS 1 so far. Our hSMS 1 model may serve as a reasonable structural basis for the discovery of more effective small-molecule inhibitors of hSMS 1.